Endogamia em um Rebanho da Raça Guzerá - De Oliveira, João Ademir [UNESP]; Bastos, João Francisco P. [UNESP]; Tonhati, Humberto [UNESP] (My University, 1999)
The objective of this study was to evaluate the effect of the inbreeding on the birth weight (BW) and the weights at the 8 (W8), 12 (W12), 18 (W18) and 24 (W24) month of age, from a Guzera breed herd. The data collected from 1978 to 1992 were obtained from the animal record control of the Fazenda de Ensino e Pesquisa do Campus de Ilha Solteira, UNESP, and referred to the weights, in the above sequence of 2435, 1882, 1770, 1424 and 1294 animals. The statistical analyses were elaborated by the least square method, using the procedure GLM (General Linear Models) of the SAS statistical software. The inbreeding coefficient in the herd ranged from 0 to 25% and 0 to 31%, respectively, for males and females, with average F of 1.08 and 1.36%, respectively. The least squares fitted means of the inbreeding and non inbreeding animals, for males and females as a set, were 27.1 and 27.2 kg, 147.7 and 148.7 kg, 183.4 and 185.4 kg, 234.5 and 238.9 kg and 292.9 and 294.7 kg for BW, W8, W12, W18 and W24, respectively. The linear regression of W8, W12 and W24 coefficients of females and W18 of males on the inbreeding coefficients were negative and significant. For males and females as a set, the differences in the weights per inbreeding class were not significant, except for W18. The effect of inbreeding on the birth weights at 24 months of age in the studied herd, in general, was of small economical or biological significance.
Inbreeding in a Guzera Breed Herd
Keywords: Guzera breed; Inbreeding; Weight